Contamination Profiles of Selected Pollutants in Procambarus clarkii Non-Edible Portions Highlight Their Potential Exploitation Applications - Dario Savoca; Mirella Vazzana; Vincenzo Arizza; Antonella Maccotta; Santino Orecchio; Francesco Longo; Vittoria Giudice; Gaetano D’Oca; Salvatore Messina; Federico Marrone; Manuela Mauro (Journal of Xenobiotics)
Properly managing aquatic organisms is crucial, including protecting endemic species and controlling invasive species. From a circular economy perspective, the sustainable use of aquatic species as a source of bioactive molecules is an area that is increasingly being explored. This includes the use of non-edible portions of seafood, which could pose considerable risks to the environment due to current methods of disposal. Therefore, it is of paramount importance to ensure that the exploitation of these resources does not result in the transfer of pollutants to the final product. This study analyzed two types of non-edible parts from the crayfish Procambarus clarkii: the abdominal portion of the exoskeleton (AbE) and the whole exoskeleton (WE), including the cephalothorax. These portions could potentially be utilized in the context of eradication activities regulated by local authorities. A screening analysis of four classes of pollutants, including pesticides, per- and polyfluoroalkyl substances (PFAS), phthalic acid esters (PAEs), and trace elements (TEs), was performed. The only analytes detected were TEs, and significant differences in the contamination profile were found between AbE and WE. Nevertheless, the levels recorded were comparable to or lower than those reported in the literature and below the maximum levels allowed in the current European legislation for food, suggesting that their potential use is legally permitted. In terms of scalability, the utilization of the entire non-edible P. clarkii portion would represent a sustainable solution for the reuse of waste products.